Complete national parks of the United States : featuring 400+ parks, monuments, battlefields, historic sites, scenic trails, recreation areas, and seashores - White, Mel, 1950- (National Geographic Soc, 2016)
From New England to Alaska, this 544 page resource is filled with helpful advice, historical background, and practical facts on how to reach scores of park system properties, when to go, and what to do there.